Multilayered PVDF-HFP Porous Separator via Phase Separation and Selective Solvent Etching for High Voltage Lithium-Ion Batteries - Van-Tien Bui; Van-Toan Nguyen; Ngoc-Anh Nguyen; Reddicherla Umapathi; Liudmila L. Larina; Jong Heon Kim; Hyun-Suk Kim; Ho-Suk Choi (Membranes, 2021)
The development of highly porous and thin separator is a great challenge for lithium-ion batteries (LIBs). However, the inevitable safety issues always caused by poor mechanical integrity and internal short circuits of the thin separator must be addressed before this type of separator can be applied to lithium-ion batteries. Here, we developed a novel multilayer poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) membrane with a highly porous and lamellar structure, through a combination of evaporation-induced phase separation and selective solvent etching methods. The developed membrane is capable of a greater amount of electrolyte uptake and excellent electrolyte retention resulting from its superior electrolyte wettability and highly porous structure, thereby offering better electrochemical performance compared to that of a commercial polyolefin separator (Celgard). Moreover, benefiting from the layered configuration, the tensile strength of the membrane can reach 13.5 MPa, which is close to the mechanical strength of the Celgard type along the transversal direction. The elaborate design of the multilayered structure allows the fabrication of a new class of thin separators with significant improvements in the mechanical and electrochemical performance. Given safer operation, the developed multilayer membrane may become a preferable separator required for high-power and high-energy storage devices.